Option C
The value of function when x = -3 is f(-3) = -3
Solution:
Given function is:
[tex]f(x) = -( -x )[/tex]
We have to evaluate the given function for x = -3
We can find the value of f(x) when x is equal to -3 by substituting -3 in place of x
Substitute x = - 3 in given function
[tex]f( -3 ) = -(- (-3))[/tex]
Solve for the innermost bracket
We have -3 inside the bracket and negative sign outside the bracket
We know that negative sign multiplied with another negative sign will give positive sign
Therefore,
[tex]f( -3 ) = -(3)[/tex]
Now we have 3 inside the bracket and negative sign outside the bracket
Negative sign multiplied with positive sign will give negative sign
Therefore,
[tex]f( -3 ) = -(3) = -3\\\\f(-3) = -3[/tex]
Thus value of function when x = -3 is f(-3) = -3